The Design of Smart Club Mobile Applications to Assist Activity Tracking and Decision Making Using Decision Tree with Forward Chaining Method - Sihotang, Jay Idoan (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
The rapid development of technology helps many organizations in carrying out organizational development. One form of organizational development is using information systems as a platform to track organizational activities and make organizational decisions. In this research, the author uses a case study of the Honda Vario Riders Club Bandung (HVRC Bandung) motorcycle club. Some activities carried out in the organization require tracking of activity participants, the actual location of the participants, and also the actualization of the calculation of the number of activities and the distance of the location. Analysis of member activities assisted by a decision tree with a forward chaining method will be a basis in determining the achievement or levels of members in the organization. The design of this application uses the Rapid Application Development System method. And in this study will discuss a technical system approach designed for an existing system, exposure of the intents involved in decision making, attributes, logic, and rules used in decision making, elaboration of technical specification requirements for application design, depiction of angular relationships of user's viewpoint of the system, further explanation of the intended relationship in the system in sequences, as well as the UI/UX design that will be used in application development. Keywords : Mobile Application, Activity Tracking, Decision Support System, Forward Chaining